Sustained Selective Attention to Competing Amplitude-Modulations in Human Auditory Cortex - Riecke, Lars (Public Library of Science, 2014)
Auditory selective attention plays an essential role for identifying sounds of interest in a scene, but the neural underpinnings are still incompletely understood. Recent findings demonstrate that neural activity that is time-locked to a particular amplitude-modulation (AM) is enhanced in the auditory cortex when the modulated stream of sounds is selectively attended to under sensory competition with other streams. However, the target sounds used in the previous studies differed not only in their AM, but also in other sound features, such as carrier frequency or location. Thus, it remains uncertain whether the observed enhancements reflect AM-selective attention. The present study aims at dissociating the effect of AM frequency on response enhancement in auditory cortex by using an ongoing auditory stimulus that contains two competing targets differing exclusively in their AM frequency. Electroencephalography results showed a sustained response enhancement for auditory attention compared to visual attention, but not for AM-selective attention (attended AM frequency vs. ignored AM frequency). In contrast, the response to the ignored AM frequency was enhanced, although a brief trend toward response enhancement occurred during the initial 15 s. Together with the previous findings, these observations indicate that selective enhancement of attended AMs in auditory cortex is adaptive under sustained AM-selective attention. This finding has implications for our understanding of cortical mechanisms for feature-based attentional gain control.